Hubungan antara Otonomi Perempuan dan Persepsi terhadap Pelayanan Konseling KB dengan Unmet Need KB pada Pasangan Usia Subur di Kecamatan Sumberjambe Kabupaten Jember (Association between Women's Autonomy and Perception of Counseling Services FP Spouses o - Dewi Febrina Paramita; Thohirun Thohirun; Ni'mal Baroya (Pustaka Kesehatan, 2017)
Indonesia is one of the developing countries that still has problem of population growth. The population of Indonesia in 2015 as much 255.5 million with a growth rate of 1.38%. The ideal number of residents of Indonesia is under 1%. One of the government's efforts to reduce the rate of population growth is to control fertility through family planning programs. Demographic and Health Survey of 2012 showed that unmet need for family planning in Indonesia is still high, that is 8.5%. Unmet need for family planning in Jember 2015 amounted to 10.4%, whereas the target RPJMN 2014 of less than 5%. Subdistrict Sumberjambe contributed the highest unmet need for family planning in Jember. This study aims to analysis relationship between women's autonomy and perceptions of family planning counseling services with unmet need for family planning in the District Sumberjambe. This study is an analytic study with cross sectional design. Total samples of 114 respondents selected by proportional random sampling technique. Bivariable analysis using Chi Square test. There is a significant relationship between the autonomy of women (OR = 3.7) and perceptions of family planning counseling services (OR = 21.60) with an unmet need family planning. Multivariate analysis using logistic regression test. It is evident that perceptions of family planning counseling services (OR = 30.678) effect on unmet need for family planning is strengthened by age, education level and employment status. Therefore proactively family planning counseling is needed. Keywords: Women’s Autonomy, Counseling FP, Unmet Need FP